Similarities in the Position of Commercial Banks and Rural Banks Regarding the Purchase of Collateral by Bad Debtors (Study of Constitutional Court Decision No:102/PUU-XVIII/2020) - Nicholas Sutrisman; Minggu Saragih; Ruben Sandi Yoga Utama Panggabean (Inspiring Law Journal, 2024)
Banks operating in Indonesia according to the Banking Law are Commercial Banks and Rural Banks. One of the business similarities between commercial banks and people's credit banks is providing credit. Something related to granting credit is the existence of collateral from the debtor's assets. If the debtor fails to carry out his obligations, the way to handle this problem is that commercial banks can purchase part or all of the debtor's collateral, while Rural Banks cannot. The different treatment or inequality before the law experienced by Rural Banks and Commercial Banks based on the provisions of Article 12 A of Law Number 10 of 1998 concerning Banking makes Rural Banks submit a Judicial Review to the Constitutional Court through constitutional case No: 102/PUU-XVIII/2020. Until the Constitutional Court granted the request for a judicial review of Article 12 A of Law No. 10 of 1998. After the Constitutional Court's decision, Rural Banks have an equal position with Commercial Banks in terms of being able to purchase part or all of debtors' collateral. The AYDA mechanism can be fully followed by BPRs as a solution to dealing with the problem of bad credit risk from debtor customers. In other words, the Constitutional Court's decision has benefits for the banking business sector in terms of handling the risk of debtors' bad credit which is a problem in banking businesses which often closes businesses